EFFECT OF DIFF. SUBS. AND SPRAYING WITH K2SIO3 ON THE ROOT AND VEGETATIVE GROWTH OF L. W. PLANTS IN BAGHDAD CITY - A. M. S. Zalzala; S. A. Abdul Latif (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate the response of two types of ornamental herbaceous plants (Wedelia trilobata and Jacobaea maritima ’Cirrus’) to different agricultural environments and the application of potassium silicates to the living walls system LWS (Felt layer system) under the climate conditions of Baghdad city. Each experiment involved the cultivation of a different plant species, and the study duration was from September 15, 2021, to August 1, 2022. A Strip-Plot Design experiment was conducted using two factors: factor M with four levels of substrates (50% peatmoss and perlite (M1), 50% Vermicompost and perlite (M2), 50% Water hyacinth compost and perlite (M3), 50% wheat straw compost and perlite (M4)) and factor S with three levels of foliar spray of potassium silicate (0, 1.5, and 3 ml Lֿ ¹) S1, S2 and S3 respectively. The results differed according to the different substrates, and the study indicators were superior using potassium silicate concentrations compared to the comparison treatment.